OEE Approach in Increasing Plant Productivity - Mariana Molina-Barrientos; Teresa Verduzco; Bernardo Villarreal (International Journal of Organizational Business Excellence, 2021)
This is the case for one of the leading conglomerates based in Spain where an unfortunate event at the group´s largest frank production plant was unable to continue working, the company adopted a sense of urgency to achieve customer demand by increasing the efficiency of the rest of its production network by 25-30%. The research focuses on describing the experience of applying the concept of Operational Equipment Effectiveness in a Spanish frankfurter plant. This approach is imbedded into a Theory of Constraints scheme that ensures a positive contribution to the objective of increasing productivity with each initiative implemented. The results show that the plant was able to produce 17,5 tons per week. Lines efficiency went up by 11%, this had not been reached since the production had risen in a 28%. The combination of important tools such as OEE and TOC, resulted in important factory level discoveries, its easy replication allowed the factory to continue a horizontal deployment to the rest of 9 franks production lines